A comparative examination of neural circuit and brain patterning between the lamprey and amphioxus reveals the evolutionary origin of the vertebrate visual center. Issue 2 (8th October 2014) - Suzuki, Daichi G.; Murakami, Yasunori; Escriva, Hector; Wada, Hiroshi
ABSTRACT Vertebrates are equipped with so‐called camera eyes, which provide them with image‐forming vision. Vertebrate image‐forming vision evolved independently from that of other animals and is regarded as a key innovation for enhancing predatory ability and ecological success. Evolutionary changes in the neural circuits, particularly the visual center, were central for the acquisition of image‐forming vision. However, the evolutionary steps, from protochordates to jaw‐less primitive vertebrates and then to jawed vertebrates, remain largely unknown. To bridge this gap, we present the detailed development of retinofugal projections in the lamprey, the neuroarchitecture in amphioxus, and the brain patterning in both animals. Both the lateral eye in larval lamprey and the frontal eye in amphioxus project to a light‐detecting visual center in the caudal prosencephalic region marked by Pax6, which possibly represents the ancestral state of the chordate visual system. Our results indicate that the visual system of the larval lamprey represents an evolutionarily primitive state, forming a link from protochordates to vertebrates and providing a new perspective of brain evolution based on developmental mechanisms and neural functions. J. Comp. Neurol. 523:251–261, 2015. © 2014 Wiley Periodicals, Inc.